TRADISI LISAN DALAM PERGESERAN DAN PEMERTAHANAN BAHASA KUI DI ALOR, NUSA TENGGARA TIMUR - Katubi Katubi (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2011)
Previous research on language shift and maintenance is commonly conductedby investigating language use from various domains. However, among theexisting domain classifcations, language use in the domain of tradition hasnever been taken into account. Meanwhile, most of existing languages in theworld have no writing system so that their continuity depends on the formof spoken language and oral tradition. This paper examines the relationshipbetween language shift/maintenance and oral tradition based on the resultof feld research about Kui language in Alor, East Nusa Tenggara. The feldresearch indicates that there is a parallelism between language shift andstagnation of transmission of oral tradition. This means that the safeguardingof endangered languages as an intangible cultural heritage should involve thesafeguarding of oral tradition. Likewise, the safeguarding of oral traditionshould involve the safeguarding of language since language is the mostsignifcant vehicle to communicate and maintain the intangible culturalheritage and knowledge indigenous.Keywords: language shift, language maintenance, oral tradition, intangibleheritage,lego-lego